Análise das decisões do CADE com uso de estudos de eventos - Fernandes, Pedro Rafael Lopes (2015)
The purpose of this research is evaluate CADE’s decisions about the mergers Santander × Real (2007), Itaú × Unibanco (2008), Gol × Webjet (2011) e Trip × Azul (2012), using the event study methodology. This methodology proposed by Eckbo (1983) lies on market efficiency’s hypothesis which says the market value of a firm reflects the present value of its expected cash flow. Hereupon, Eckbo (1983) argues that anticompetitive mergers are good also for rivals of the merging firms. Since the price increases of merging firms also enables rivals to increase their own price. So, if the market assess the merger as anticompetitive, the rival firm’s stocks will increase with the announcement of this transaction. The results demonstrate a high level of efficiency of CADE’s decisions.